1983
DOI: 10.1029/gl010i001p00039
|View full text |Cite
|
Sign up to set email alerts
|

Altitude, thickness and charge concentration of charged regions of four thunderstorms during trip 1981 based upon in situ balloon electric field measurements

Abstract: Balloon borne corona probes designed to measure vertical electric fields have yielded data on the vertical electric structure of four thunderstorms studied during the Thunderstorm Research International Program (TRIP), 1981. All four thunderclouds exhibited a bipolar charge structure with an upper positive charge region and a lower negative charge region. The negative region was consistently centered between the 0° C and −10° C isotherm altitudes. The altitudes of the concentrated positive regions varied consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 9 publications
3
19
0
Order By: Relevance
“…Flights through 4 thunderstorms showed a bipolar charge structure with a lower negative charge region, and upper positive charge region. The negative charge region was consistently located between 0 and -10°C, with a vertical depth of ≈1km, and average charge densities from -0.7 to -1.8 nCm In contrast to the bipolar charge structure measured by Byrne et al (1983), Marshall and Rust (1991) found that from 12 profiles through thunderstorms there were typically between 4 and 10 distinct charge layers, of vertical depth 130m to 2100m, with charges ranging from 0.2 to 13 nCm . Measurements of electric field were made from a balloon platform, using the EFM.…”
Section: Mature Stagementioning
confidence: 79%
See 3 more Smart Citations
“…Flights through 4 thunderstorms showed a bipolar charge structure with a lower negative charge region, and upper positive charge region. The negative charge region was consistently located between 0 and -10°C, with a vertical depth of ≈1km, and average charge densities from -0.7 to -1.8 nCm In contrast to the bipolar charge structure measured by Byrne et al (1983), Marshall and Rust (1991) found that from 12 profiles through thunderstorms there were typically between 4 and 10 distinct charge layers, of vertical depth 130m to 2100m, with charges ranging from 0.2 to 13 nCm . Measurements of electric field were made from a balloon platform, using the EFM.…”
Section: Mature Stagementioning
confidence: 79%
“…This instrument measures the corona-point discharge current induced through a conducting wire by the electric field, and is described by Weber and Few (1978), and Weber et al (1983). Flights through 4 thunderstorms showed a bipolar charge structure with a lower negative charge region, and upper positive charge region.…”
Section: Mature Stagementioning
confidence: 99%
See 2 more Smart Citations
“…This characteristic of leader and return stroke fields (static fields) provides information to estimate the charge source heights. Taking measurements by balloon-borne instruments is also a popular method [27][28][29][30]. In some cases more than one of these techniques are applied to obtain more precise information.…”
Section: Introductionmentioning
confidence: 99%